Examining the Cointegrating and Causality Relationship between Foreign Portfolio Investments and the Securities Market Returns at the Botswana Stock Exchange - Ntshole , Thabang; Chiwira, Oscar (International Journal of Economics and Financial Issues, 2026)
In the context of Botswana, the relationship between foreign portfolio investment and the stock market returns is unclear in both the short and long run. The study aims to empirically examine the relationship between foreign portfolio investments and securities markets performance at the Botswana Stock Exchange (BSE), covering the period 2004 to 2022. The study employed the Autoregressive Distributed Lag (ARDL) Bounds model to test for cointegration and the Toda and Yamamoto and Dolado and Lütkepohl (TYDL) model to examine the direction of causality. The findings suggest that current investment flows significantly enhance current stock market returns in the short run; considering macroeconomic factors such as interest rates, market capitalization and exchange rates. The study also finds that past investment flows do not Granger cause stock market returns, indicating that past investment flows do not contain sufficient information to predict future stock returns and past stock returns do not predict future investment flows. The BSE is urged to enhance data transparency and availability, implement risk management frameworks, improve financial market infrastructure, support capital market development, monitor and manage volatility as well as developing strategies to attract stable foreign investment.